Análisis del nivel de voltaje del alimentador “SALCEDO – CENTRO”, de la subestación Salcedo. - Cocha Maiquiza, Cristian Alexander (2019)
The delivery companies of the Ecuador, have to provide electric service quality taking into account the income of new demand to the system, maintaining security in its electrical infrastructure, reliability and continuity of service both in the primary circuits and its secondary circuits and their respective transformers. This Research project based on the analysis of the voltage level of the 03SA13B1S2 Feeder "Salcedo - Centro" belonging to Empresa Eléctrica Cotopaxi SA. The study was based on the data collection where the number of transformers were announced with their respective capacities and the existing users in the respective feeder, the information was obtained through two stages. The first stage is constituted by the identification of the path of the feeder and its respective transformers through the SIG Geoportal platform, the secondary stage is constituted by the information of the system loads information that was requested from the different Departments (Planning, Technical and Commercial) of ELEPCO SA. The POWER WORLD software was used for modeling the feeder in which each of the data obtained from the system was entered, through modeling performed, the current status of the feeder and the respective analysis of the voltage level in which the system is found to be the case and the voltage levels are outside the ranges allowed by the company, viable technical and economic alternatives will be made available to improve the voltage profile.